Readiness of Higher Education Institutions for Digital Transformation Processes - A. N. Markov; S. A. Migalevich (Цифровая трансформация)
The article discusses the experience of development and transformation of internal information systems of higher education institutions of cards in the education system of the Republic of Belarus. The basic principles of digitalization are considered, taking into account the existing approaches. Higher education institutions have their own internal integrated information systems for managing the educational process and the educational institution as a whole. Integration of access control systems, uniform cards of students and employees of educational institutions with perimeter control into IIS "University", information protection of internal resources and IIS as a whole will significantly accelerate the digitalization of educational institutions, and as a result, a faster transition to the digital economy.